A força-invenção da docência e da infância nos processos de aprenderensinar - Lourenço, Suzany Goulart (2015)
It aims to problematize the power of force-invention of learnig-teaching processes experienced in school space-times. It is a mapping of teacher’s and children’s experiences, produced in a Municipal Elementary School in Serra/ES, which translates the monitoring knowlegde-action networks woven into the everyday life in school by these people. Such monitoring was produced through observations, journaling field, photographic and audio, as well as conversations with the children and teachers. It aims to understand what is being produced as power of life at school, from the experiences and inventions of those who actthink the school routine. Its main theoretical intercessors are Gilles Deleuze, Félix Guattari, Michel Foucault, Peter Pelbart and Jorge Larrosa, which help to think about the possibilities of a limit-experience to overcome the dogmatic image of thought and to the enhancement of curriculum movements. The concepts of experience in Larrosa and force-invention in Pelbart indicate gaps for Curriculum-Experience-Invention. This one, thought on the immanence of daily school life, shows that it is possible and necessary to be in school betting on good encounters and joyful affections